Characterization and Levels of Expression of Sensory Neuron Membrane Proteins in the Adult Citrus Fruit Fly (Diptera: Tephritidae). Issue 6 (27th November 2018) - Zhang, Guohui; Chen, Jian; Wang, Fulian; Gui, Lianyou; Zhang, Jianming
Abstract: Sensory neuron membrane proteins (SNMPs) play an important role in insect chemoreception; however, the SNMPs for Bactrocera minax (Enderlein) (Diptera: Tephritidae), an economically important pest of citrus, remain uncharacterized. Here, we report on the molecular characterization of SNMPs ( BminSNMP1 and BminSNMP2 ) from adult B. minax . The open-reading frames of BminSNMP1 and BminSNMP2 were 1, 608 and 1, 647 nucleotides, encoding proteins of 535 and 557 amino acid residues, respectively. Phylogenetic analysis showed that the two BminSNMPs belonged to two distinct subgroups, indicating the possibility of their contrasting function in insect chemoreception. Real-time PCR results showed that BminSNMP1 was expressed primarily in the antennae of males and females, where levels of expression were similar at different developmental stages of females, but lower in 1- and 5-d-old males than in 15- and 20-d-old males. In both sexes, BminSNMP2 was expressed at high levels in antennae and in nonolfactory tissues, especially in legs, where levels were higher than in other nonolfactory tissues. We found highest levels of expression of BminSNMP2 in antennae of both sexes in 30-d-old adults, while in legs of both sexes, highest levels of expression were detected in 1- and 30-d-old adults. We discuss the possible physiological functions of BminSNMPs based on our findings.